Effects of daily porcine somatotropin administration on the lysine requirement of growing pigs - G E Fitzner; T L Weeden; K G Friesen; Robert H Hines; Jim L Nelssen; Robert D Goodband; Donald H Kropf; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1991)
One-hundred twenty crossbred barrows initially weighing 68.7 lb were used to determine the lysine requirement of growing pigs injected with 5 mg/d porcine somatotropin (PST) during a 5-wk growth trial. Pigs received one of six levels of dietary lysine (.7, 1.1, 1.5, 1.9,2.3, or 2.7%) and were injected daily with either 5 mg pST or placebo. During the 5 wk trial, pST-injected pigs had increased average daily gain (ADG), decreased average daily feed intake (ADFI), and improved feed conversion (F/G) compared with placebo-injected pigs. With increasing dietary lysine, ADFI of pigs injected with both pST and placebo was reduced. Pigs injected with pST had improved ADG as dietary lysine increased to 1.5% and improved F/G as dietary lysine increased to 1.9 %. Dietary lysine had no effect on ADG or F/G of placebo-injected pigs. Pigs injected with pST had improved average backfat, tenth rib fat depth, and longissimus area compared to placebo-injected pigs. Tenth rib fat depth of both placebo- and pST-injected pigs was reduced as dietary lysine increased. Longissimus area of pST-injected pigs improved as dietary lysine increased to 1.5%. The improvements in ADG, ADFI, F/G, and longissimus area of pST-injected pigs indicate that the dietary lysine requirement of growing pigs injected with 5 mg/d pST is 1.5 to 1.9%.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; GF; Repartition; Performance; Carcass; Lysine